2006
DOI: 10.1002/mrd.20652
|View full text |Cite
|
Sign up to set email alerts
|

Development and pattern of mRNA relative abundance of bovine embryos cultured in the isolated mouse oviduct in organ culture

Abstract: The aim of this study was to examine the development of bovine zygotes in isolated mouse oviducts (IMO) and the quality of the blastocysts produced. In vitro produced bovine zygotes were transferred into the ampullae of the IMO and cultured in SOF or KSOM. Control embryos were cultured in droplets of the same media. Following 6 days of culture, blastocysts were processed for nuclei counts or mRNA abundance. Culture in the IMO did not affect the proportion of zygotes developing to the blastocyst stage compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 40 publications
1
27
1
2
Order By: Relevance
“…While embryos can be produced in the absence of exposure to the oviductal environment, it is clear that the oviduct plays an important function in fertilization and early embryo development. Several studies have demonstrated that embryos cultured in the oviducts of sheep (Lazzari et al 2002, Rizos et al 2002, cattle (Fair et al 2001, Tesfaye et al 2007 or mice (Rizos et al 2007) are of superior quality than those produced in vitro, in terms of morphology, gene expression, cryotolerance and pregnancy rate after transfer, indicating that the oviduct is not merely an organ through which gametes and embryos transit. Despite significant research, most of the pathways and oviductal factors implicated in the crosstalk between the gametes/early embryo(s) and the oviduct remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…While embryos can be produced in the absence of exposure to the oviductal environment, it is clear that the oviduct plays an important function in fertilization and early embryo development. Several studies have demonstrated that embryos cultured in the oviducts of sheep (Lazzari et al 2002, Rizos et al 2002, cattle (Fair et al 2001, Tesfaye et al 2007 or mice (Rizos et al 2007) are of superior quality than those produced in vitro, in terms of morphology, gene expression, cryotolerance and pregnancy rate after transfer, indicating that the oviduct is not merely an organ through which gametes and embryos transit. Despite significant research, most of the pathways and oviductal factors implicated in the crosstalk between the gametes/early embryo(s) and the oviduct remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, shortterm culture of in vitro produced zygotes in the oviducts of sheep (Enright et al, 2000;Rizos et al, 2002), cattle (Tesfaye et al, 2007) or even mice (Rizos et al, 2007 and has been shown to improve embryo quality, measured in terms of morphology, gene expression, cryotolerance and pregnancy rate after transfer. In contrast, relatively little evidence exists of an effect going the other way (embryo to oviduct).…”
Section: Introductionmentioning
confidence: 99%
“…The oviductal environment can support embryonic growth up to the blastocyst stage across a wide range of species following trans-species transfer (Rizos et al 2007). Culture of cow embryos in the oviduct of the ewe is suitable for the development of embryos from the zygote to blastocyst stage and even through the early stages of elongation.…”
Section: Heterologous Versus Homologous Culturementioning
confidence: 99%